Case Report: Erroneous Human Immunodeficiency Virus-1 Diagnosis in a Pregnant Woman Using Centers for Disease Control and Prevention Diagnostic Algorithm. (9th August 2022) - Hastie, Elizabeth; Stangl, Lisa; Deutsch, Karen; Yin, Jeffrey; Hull, Andrew; Spector, Stephen A; Blumenthal, Jill
Abstract: We describe a case of a pregnant cisgender woman diagnosed with human immunodeficiency virus (HIV)-1 using the current Centers for Disease Control and Prevention diagnostic algorithm who subsequently had her diagnosis overturned after additional testing outside of the algorithm, including an HIV-1 proviral deoxyribonucleic acid test that was negative.